PENGARUH JUMLAH UANG BEREDAR, PEMBAYARAN NONTUNAI DAN BI RATE TERHADAP INFLASI DI INDONESIA - Angelica Putri Wijaya; Indri Arrafi Juliannisa (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Inflation is a monetary phenomenon that can be used as a reference to see the condition of the economy in Indonesia, so that its stability must be maintained for the sustainability and welfare of its people. The purpose of this study is to find out how the money supply affects, non-cash payments (electronic money and APMK) as well as the BI Rate on Inflation in Indonesia. The study sample from 2012 to 2020 using monthly data of 108 data. This study used Eviews 10 using Error Correction Model analysis using time series data. The data is sourced from publications by the Central Statistics Agency and Bank Indonesia. The results showed that (1) JUB does not have a significant effect on inflation in Indonesia in the long term and short term, (2) Electronic Money has no significant effect on inflation in Indonesia in the long term and short term, (3) APMK has a significant effect on inflation in Indonesia in the long term and short term, (4) The BI Rate has a significant effect on inflation in Indonesia in the long term and short term.